(untitled) (International Seven Journal of Multidisciplinary, 2024)
The aim of this essay is to explain the concept of entrepreneur to the layman, who has no commitment to the scientific world, but utters everyday words in a general sense. The methodology used is research into scientific books, written over time, when the form of negotiation differs, in an attempt to understand how this term arose and is linked to normal economic relations. The interesting thing is that trade in a society has grown a lot, with a different conception of the term entrepreneur, which increases with the opening of businesses that trade in someone’s surplus products. Thus, we will analyze the entrepreneur and his history, in all its details throughout the ages, which society needs, and is offered by someone outside the family; hence, it is concluded that any person not involved in direct production, acts in the market in an indirect way.